Sodium Solute Symporter and Cadherin Proteins Act as Bacillus thuringiensis Cry3Ba Toxin Functional Receptors in Tribolium castaneum - Contreras, Estefanía (American Society for Biochemistry and Molecular Biology, 2013)
Understanding how Bacillus thuringiensis (Bt) toxins interact with proteins in the midgut of susceptible coleopteran insects is crucial to fully explain the molecular bases of Bt specificity and insecticidal action. In this work, aminopeptidase N (TcAPN-I), E-cadherin (TcCad1), and sodium solute symporter (TcSSS) have been identified by ligand blot as putative Cry3Ba toxin-binding proteins in Tribolium castaneum (Tc) larvae. RNA interference knockdown of TcCad1 or TcSSS proteins resulted in decreased susceptibility to Cry3Ba toxin, demonstrating the Cry toxin receptor functionality for these proteins. In contrast, TcAPN-I silencing had no effect on Cry3Ba larval toxicity, suggesting that this protein is not relevant in the Cry3Ba toxin mode of action in Tc. Remarkable features of TcSSS protein were the presence of cadherin repeats in its amino acid sequence and that a TcSSS peptide fragment containing a sequence homologous to a binding epitope found in Manduca sexta and Tenebrio molitor Bt cadherin functional receptors enhanced Cry3Ba toxicity. This is the first time that the involvement of a sodium solute symporter protein as a Bt functional receptor has been demonstrated. The role of this novel receptor in Bt toxicity against coleopteran insects together with the lack of receptor functionality of aminopeptidase N proteins might account for some of the differences in toxin specificity between Lepidoptera and Coleoptera insect orders.